Exploring Association Between Social Media Addiction, Fear of Missing Out, and Self-Presentation Online Among University Students: A Cross-Sectional Study - Zhu, Xinhong; Xiong, Zhenfang (Frontiers in Psychiatry, 2022)
Background: Social media addiction (SMA) is known to be associated with excess use of social media. However, few studies have focused on the links of self-presentation on social media, fear of missing out (FoMO) and SMA. The present study investigated the relationships of self-presentation, FoMO and SMA among university students. Methods: Online survey was conducted with 2744 respondents, who completed online survey including social media use, FoMO and SMA. Self-presentation on social media and privacy information protection were assessed via researcher-designed questionnaires. Self-presentation on social media was composed of basic information shown on social media and expression willingness. Privacy information protection contained information viewed by others and privacy settings in social media platforms. Results: The most common information posted on social media were gender, hobby, age, personal photos and videos, and birthday. The most common social platforms with privacy setting were QQ zone (62.2%), WeChat (60.1%), and QQ (40.3%). FoMO (OR = 2.852, P = 0.000), information viewed by others (OR = 4.261, P = 0.000), managing a personal homepage (OR = 1.339, P = 0.002), accept a stranger’s “friend request” (OR = 1.251, P = 0.028) and undergraduate students and above (OR = 1.439, P = 0.001) predicted expression willingness. FoMO (OR = 5.278, P = 0.000), information viewed by others (OR = 9.673, P = 0.000), privacy setting in QQ (OR = 0.817, P = 0.002) and in Tik Tok (OR = 0.536, P = 0.019) and female (OR = 0.588, P = 0.004) significantly influenced basic information shown on social media. Furthermore, FoMO (OR = 4.165, P = 0.000), expression willingness (OR = 1.645, P = 0.000), and information viewed by others (OR = 1.406, P = 0.000) positively affected the level of SMA. Risk of SMA increased as time spent on social media per day. However, basic information shown on social media did not significantly influence SMA. Conclusion: In general, students with higher level of FoMO and expression willingness are more likely to experience SMA. These results highlight individual behaviors on social media should be considered as essential elements for assessing problematic engaging to social media.